Disiplin Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan Serta Motivasi Sebagai Variabel Moderasi Pada PT. Ilham Jaya Lestari Palembang - Marizka, Hany; Lazuarni, Shafiera; Veronica, Meilin (Jurnal Dinamika Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of work discipline and compensation on employee productivity with motivation as a moderating variable at PT. Ilham Jaya Lestari. The research method used is quantitative with a survey approach through the distribution of questionnaires to 112 respondents. Data analysis techniques include multiple linear regression and Moderated Regression Analysis (MRA) to test the moderation effect. The results show that work discipline and compensation have a positive and significant influence on employee productivity. Additionally, motivation is proven to strengthen the relationship between work discipline and compensation on productivity. This indicates that increasing motivation can enhance the effectiveness of work discipline and compensation in driving employee productivity. The implications of this study suggest that the company needs to improve work discipline through stricter policies and a fairer, performance-based compensation system. Furthermore, the company is advised to strengthen employee motivation through incentives and creating a more conducive work environment. This study contributes to Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth. By understanding the factors that influence employee productivity, the findings help the company design fairer and performance-based policies regarding compensation and work discipline. Additionally, increasing employee motivation can support the creation of a healthier, more productive, and sustainable work environment, aligning with SDG 8's goal of improving labor productivity and employee well-being